PERANAN KEPEMIMPINAN DALAM BIROKRASI DI DINAS KEHUTANAN KABUPATEN KUTAI TIMUR - Erni Kusumawati (Jurnal Paradigma (JP), 2017)
The leading role in the bureaucracyin in Foresty Department in East Kutai are implemented as its function. Nevertheless there are some focus still not implemented effectively. But applicative has showed good indication. The header of Foresty Department of East Kutai doesn’t work optimally reflected on 6 (six) research sub focus which applied, the fact all of roles are not implemented effectively yet, especially the role as facilitator and the role as innovator are not doing well yet, whereas another role as innovator indicate effective. The leading role is not optimal becaused authority limit of Department’s header seeks demand subordinate which concern work facilities nor doing renewal towards apparatus’ mindset through capacity enhancement and apparatus competence.